PERANCANGAN BACKEND MODULAR DAN REUSABLE UNTUK SISTEM SUPER ADMIN PADA APLIKASI LOMBOK HALAL ROOM DENGAN RESTFUL API - Muhamad Singgih; Royana Afwani; Ramaditia Dwiyansaputra; Mochammad Dinta Alif Syaifuddin (IDEALIS : InDonEsiA journaL Information System, 2026)
The growth of halal tourism in Lombok, Indonesia, calls for scalable digital platforms with strong and centralized administrative governance. This study proposes and implements a domain-oriented, modular RESTful API backend to support Super Admin operations in the Lombok Halal Room (LHR) platform. Using a design-science approach and an iterative SCRUM process, we developed a layered API Service Repository Infrastructure architecture using Hapi.js, PostgreSQL, and Redis, delivering 42 endpoints across key administrative domains with uniform JSON contracts and JWT-based authentication. The proposed contribution is a metric-driven engineering template that links SCRUM execution to modular backend domains and validates the resulting system using performance and software-quality measurements. Experimental results under controlled workloads show that Redis caching substantially improves scalability for read-heavy administrative operations by reducing response time from seconds to low single-digit milliseconds and increasing throughput to above 40,000 requests per second. Code-quality metrics further indicate clean module boundaries (CBO=0; LCOM*=0), while the Maintainability Index (MI) highlights modules that require targeted refactoring. Overall, the backend provides a reusable reference architecture for centralized halal tourism administration such as partner verification, content moderation, transaction oversight, and system monitoring that can be adapted to similar platforms in other regions.